Diacetyl strategy for synthesis of NHAc containing glycans: enhancing glycosylation reactivity via diacetyl imide protection - Fukase, Koichi; Manabe, Yoshiyuki; Shimoyama, Atsushi (Frontiers in Chemistry, 2023)
The presence of NHAc groups in the substrates (both glycosyl donors and acceptors) significantly reduced the reactivity of glycosylation. This decrease was attributed to the NHAc groups forming intermolecular hydrogen bonds by the NHAc groups, thereby reducing the molecular mobility. Hence, a diacetyl strategy involving temporary conversion of NHAc to diacetyl imide (NAc2) was developed for the synthesis of NHAc-containing glycans. This strategy has two significant advantages for oligosaccharide synthesis. The NAc2 protection of NHAc substantially enhances the rate of glycosylation reactions, resulting in improved yields. Moreover, NAc2 can be readily reverted to NHAc by the simple removal of one acetyl group under mild basic conditions, obviating the necessity for treating the polar amino group. We have achieved efficient synthesis of oligosaccharides containing GlcNHAc and N-glycans containing sialic acid using the diacetyl strategy.